An effective green and renewable heterogeneous catalyst derived from the fusion of bi‐component biowaste materials for the optimized transesterification of linseed oil methyl ester. (4th June 2021) - Etim, Anietie O.; Musonge, Paul; Eloka‐Eboka, Andrew C.
Abstract: Biological waste materials are rich sources of important minerals such as calcium and potassium, which are required in the preparation of effective biocatalysts for biodiesel production. Their adoption into green catalyst production is becoming important due to the ease of process synthesis and the availability of waste animal shells and agricultural materials. In this study, the potential of a bi‐component, heterogeneous catalyst of fused chicken eggshells and pawpaw peels was tested in the transesterification reaction of linseed oil. The waste materials, separately, were dried and calcined at 900 °C or at 700 °C for 3 h to obtain their calcined ashes (calcined eggshells (CES) and calcined pawpaw peels (CPP)). The CES and CPP were then bonded by the wet impregnation method (by dissolving each ash at weight concentration of 7:3 CES/CPP in 100 mL warm distilled water and further calcining them at 600 °C for 2 h). The catalyst that was developed was characterized using Scanning Electron Microscopy ‐ Energy Dispersive X‐Ray Spectroscopy (SEM–EDX), X‐ray diffraction (XRD) and Fourier transform infrared spectroscopy (FTIR). The Box–Behnken design was applied to generate 15 experimental runs, which were used to investigate the effect of the operational parameters such as methanol‐to‐oil molar ratio, catalyst loading, and reaction time. The characterization results show that the ash is very rich in Ca and K ions. The best reaction condition for the transesterification process was found to be a methanol / oil molar ratio of 14.9:1, catalyst loading of 3.78 wt%, process reaction time of 80 min at constant reaction temperature of 65 °C with a biodiesel maximum yield of 91.20 wt%. The physicochemical properties of the produced biodiesel were measured and found to meet the American Society for Testing of Materials (ASTM) and European National (EN) standards and South African National Standards (SANS) biodiesel quality standards. The fused catalyst can be reused for up to five cycles with little reduction in yields. The study demonstrates the potential of utilizing biomass feedstock in developing effective and sustainable biodiesel fuels. © 2021 Society of Chemical Industry and John Wiley & Sons, Ltd